The convention of lomé — Towards a new international cooperation? - Hajo Hasenpflug (Intereconomics, 1975)
The relations between 46 developing countries and the EC had to be reviewed and revised after the expiry of the EC association agreements with the 19 Yaoundé states and the three Arousha states and also because of the accession of Great Britain to the EC which made it necessary to include also the LDCs of the Commonwealth.
Keywords: 330; Association Policy